The Influence of Curriculum Adaptation and Intercultural Communication on the Understanding of Indonesian Biodiversity in Aichi University of Education Affiliated Senior High School Japan Through the Student Teaching Practice Program - Berliana, Halida Zia; Harlita, Harlita (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to determine the influence of curriculum adaptation and intercultural communication on the understanding of Indonesian biodiversity through the student teaching practice program in Aichi University of Education Affiliated Senior High School, Japan. This type of research employs an experimental design with a quantitative approach. Data were obtained through questionnaires with actions carried out during teaching practice. Analysis was carried out using multiple linear regression and path analysis. The results show that there is a significant influence of intervention from teaching practice teachers on the understanding of Indonesian Biodiversity. This article assesses the impact of variable X1 (curriculum adaptation) and variable X2 (communication between people of different cultures) on Y (understanding of Indonesian biodiversity in Japanese students) by considering the intervention (Z) of teaching practice students as a strategic mediator connecting the two. The study confirmed that student intervention in teaching practice acts as an effective mediator in improving understanding of Indonesian biodiversity. Curriculum adaptation (X1) and cross-cultural communication (X2) significantly influence Japanese students' understanding (Y), both directly and indirectly through intervention (Z), thus strengthening the effectiveness of contextual and intercultural learning.